2020
DOI: 10.1021/acsbiomaterials.9b00968
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Assisted Photodynamic Therapy Based on Nanomaterials

Abstract: Photodynamic therapy (PDT) is a noninvasive cancer treatment that requires the copresence of a photosensitizer (PS), oxygen, and light. The efficacy of conventional PDT is usually limited by two factors: delivery of the PS to the tumor and the hypoxic solid tumor environment. To improve the efficacy of PDT, nanomaterial-based, enzyme-assisted PDT (nano-ezPDT), which integrates enzyme-responsive components into nanomedicines, was developed for enhanced PS delivery and oxygen generation. Nano-ezPDT is designed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 102 publications
0
17
0
Order By: Relevance
“…In the second form, PDT itself causes rapid inhibition of the tumor vasculature, leading to rapid depletion of the local oxygen supply 87 . In any case, solid tumors with a high percentage of hypoxic cells have strong resistance to PDT, making it very difficult to continuously perform PDT 88 . The key molecular mechanism of hypoxia begins with the activation of hypoxia-inducible factor-1 (HIF-1), which is a major effector and transcriptional regulator.…”
Section: Introductionmentioning
confidence: 99%
“…In the second form, PDT itself causes rapid inhibition of the tumor vasculature, leading to rapid depletion of the local oxygen supply 87 . In any case, solid tumors with a high percentage of hypoxic cells have strong resistance to PDT, making it very difficult to continuously perform PDT 88 . The key molecular mechanism of hypoxia begins with the activation of hypoxia-inducible factor-1 (HIF-1), which is a major effector and transcriptional regulator.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, numerous recent studies have utilized catalase to increase the efficiency of photodynamic therapy by resolving tumor hypoxia through oxygen production, but they are not of interest in this article. [ 102 ] Simple loading of catalase into polymeric NPs is a straightforward approach for the protection of the enzyme. An early study has demonstrated that encapsulating catalase into PEG–PLGA NPs can retain enzymatic activity under protease conditions.…”
Section: Polymer‐based Delivery Of Antioxidantsmentioning
confidence: 99%
“…Upregulation of endogenous enzymes on the surface of tumor environment for O 2 generation heavily trusts on catalase loaded nanocarriers for which understanding the strategic role of PDT in the presence of a photosensitizer (PS), oxygen, and light is essential especially for non‐invasive cancers. [ 159 ] In this context, the release of the enzymes and its control in the TME including self‐acceleration mechanism is required to understand. A greater control over systemic toxicity in a deoxygenation‐activated chemotherapy can be achieved for which nanoclustered cascaded enzymes paves an avenue.…”
Section: Perspectivesmentioning
confidence: 99%